فعالية برنامج تدريبي في رفع مستوى معرفة المعلمات بمهارات تقرير المصير المقدمة للتلميذات ذوات الإعاقة الفكرية - الشلوي، إيمان فالح علي Alshalawi, Iman Faleh Ali (جامعة عين شمس - كلية التربية, 2022)
هدفت هذه الدراسة إلى الكشف عن فاعلية برنامج تدريبي في تعزيز مستوى معرفة المعلمات بمهارات تقرير المصير للتلميذات ذوات الإعاقة الفكرية، وقد اعتمدت المنهج شبه التجريبي، وتمثلت أدوات الدراسة في: برنامج تدريبي لزيادة مستوى المعرفة بمهارات تقرير المصير، واشتملت عينة الدراسة على (62) معلمة من معلمات التربية الفكرية في مدارس المرحلة الثانوية الملحق بها برامج للتربية الفكرية بمدينة الرياض وقسموا إلى: 31 في المجموعة التجريبية، 31 في المجموعة الضابطة)، وقد تم تصميم برنامج تدريبي لزيادة مستوى المعرفة بمهارات تقرير المصير واختبار مستوى معرفة المعلمات بمهارات تقرير، وقد توصلت الدراسة إلى العديد من النتائج أهمها: عدم وجود فروق ذات دلالة إحصائية بين المجموعة الضابطة والتجريبية في مستوى المعرفة لدى المعلمات بمهارات تقرير المصير للتلميذات ذوات الإعاقة الفكرية وفقا لنتائج القياس القبلي. إضافة إلى وجود فروق ذات دلالة إحصائية بين المجموعة الضابطة والتجريبية في مستوى المعرفة لدى المعلمات بمهارات تقرير المصير للتلميذات ذوات الإعاقة الفكرية وفقا لنتائج القياس البعدي لصالح المجموعة التجريبية، ووجود فاعلية للبرنامج التدريبي على زيادة مستوى المعرفة لدى المعلمات بمهارات تقرير المصير للتلميذات ذوات الإعاقة الفكرية. This study aimed to reveal the effectiveness of a training program in enhancing the level of female teachers’ knowledge of self-determination skills for female students with intellectual disabilities. It adopted the quasi-experimental approach. The study tools consisted of: a training program to increase the level of knowledge of self-determination skills, and the study sample included (62) female intellectual education teachers in secondary schools with intellectual education programs in Riyadh. A training program was designed to increase the level of knowledge of self-determination skills and to test the level of female teachers’ knowledge of self-determination skills, and the study reached several results, the most important of which are: There are no statistically significant differences between the control and experimental group in the level of female teachers’ knowledge of self-determination skills for students with intellectual disabilities. According to the pretest results. In addition to the presence of statistically significant differences between the control and experimental group in the level of knowledge of female teachers of self-determination skills for female students with intellectual disabilities, according to the results of the post-measurement in favor of the experimental group, and the existence of the effectiveness of the training program on increasing female teachers’ level of knowledge of self-determination skills for female students with intellectual disabilities.
Keywords: التربية الخاصة -- التربية الفكرية -- مهارات تقرير المصير -- ذوو الإعاقة الفكرية -- معلمو المرحلة الثانوية